Sexual Violence in Higher Education, Policies in Indonesia and India - Sukeni, Dewi Setyowati; Bhanu Prakash (JUSTITIA JURNAL HUKUM, 2023)
The phenomenon of sexual violence in college is a serious concern of the Ministry of Education and Culture, and in order to prevent and handle the occurrence of sexual violence in college, the Minister of Education and Culture Regulation Number 30 Year 2021 concerning Prevention and Handling of Sexual Violence in Higher Education is issued (hereinafter referred to as Permendikbud 30 / 2021) which was promulgated on September 30, 2021. The enactment of Permendikbud 30 / 2021 raises pros and cons in the community such as the enactment of provisions regarding "sexual consent" or "without the consent of the victim" as stated in Article 5 that for several acts that are included the category of harassment if it is carried out with the consent of the victim then it can be justified or not harassment, for example the act of spreading images or photos of victims that have sexual nuances. The Prevention of Sexual Harassment Act came into force in India after what is known as the Nirbhaya case. It makes it compulsory for all higher education institutions to have an internal complaints committee (ICC) to address abuse on campus. But nearly, a report by the Ministry of Education found only 95 out of 188 institutions had established committees, and those that were in place were considered ineffectual by students.This study aims to determine, identify and analyze the position of the Minister of Education and Culture Regulation Number 30 Year 2021 in the material criminal law system in Indonesia; to find out and describe how the implementation of Permendikbud 30 / 2021, especially with regard to aspects of handling sexual violence in universities. Normative juridical research using the approach to legislation and the implementation of the Minister of Education and Culture Regulation must begin with strengthening higher education governance such as the establishment of a task force for the prevention and handling of sexual violence, preparation of guidelines for the prevention and treatment of sexual violence, provision of reporting services, counseling for victims, socialization in college environment. Keywords: prevention, treatment, sexual violence, college.